The Focused Future of Healthcare: What is the Attention Mechanism in Medical AI? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Focused Future of Healthcare: What is the Attention Mechanism in Medical AI? The integration of Artificial Intelligence (AI) into medicine is rapidl...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine